“Learning on a chip:” Microfluidics for formal and informal science education - Rackus, Darius G. (Biomicrofluidics, 2019)
Microfluidics is a technique for the handling of small volumes of liquids on the order of picoliters to nanoliters and has impact for miniaturized biomedical science and fundamental research. Because of its multi- and interdisciplinary nature (i.e., combining the fields of biology, chemistry, physics, and engineering), microfluidics offers much potential for educational applications, both at the university level as well as primary and secondary education. Microfluidics is also an ideal “tool” to enthuse and educate members of the general public about the interdisciplinary aspects of modern sciences, including concepts of science, technology, engineering, and mathematics subjects such as (bio)engineering, chemistry, and biomedical sciences. Here, we provide an overview of approaches that have been taken to make microfluidics accessible for formal and informal learning. We also point out future avenues and desired developments. At the extreme ends, we can distinguish between projects that teach how to build microfluidic devices vs projects that make various microscopic phenomena (e.g., low Reynolds number hydrodynamics, microbiology) accessible to learners and the general public. Microfluidics also enables educators to make experiments low-cost and scalable, and thereby widely accessible. Our goal for this review is to assist academic researchers working in the field of microfluidics and lab-on-a-chip technologies as well as educators with translating research from the laboratory into the lecture hall, teaching laboratory, or public sphere.